Influence of foreign television on Caribbean people - Hoyte, Harold (Caribbean Publishing and Broadcasting Association [S.l.], 1986)
Reviews studies done over the past 10 years on various areas of the region's media systems. Expresses concerns of the Caribbean Publishing and Broadcasting Association relating to the quantity, content and effects of foreign programming on the regional populace. Concludes that national and regional communications policies must be established in order to clear the way for the creation of alternative means of intra-regional communications. Recommends inter alia, joint CARICOM action to establish a regional broadcasting and telecommunications authority to ensure that the airwaves are used for regional integration and not cultural emasculation.